Hubungan kecemasan dalam menghadapi evaluasi belajar bahasa Indonesia dengan efikasi diri siswa kelas 4 SD Negeri 1 Kadipiro Bantul - Saputra, Hanafi Arum; Akbar Al Masjid; Biya Ebi Praheto (Universitas Sarjanawiyata Tamansiswa, 2024)
This research is a quantitative study using the Spearman Rank correlation test to evaluate the non-parametric relationship between evaluation anxiety and self-efficacy of class 4 A students at SD Negeri 1 Kadipiro Bantul. The collection technique in this research used interviews, documentation, and distribution of questionnaires. Data analysis techniques use descriptive analysis, normality test, linearity test, and hypothesis test. The research results showed that the average score for evaluation anxiety was 54.48 or in the medium category, and the results of self-efficacy showed an average score of 31.72, which was in the medium category. The results of the Spearman Rank correlation analysis test show a correlation value of -0.388, so it can be concluded that there is a negative relationship between the variable evaluation anxiety and self-efficacy, which means that the higher the level of anxiety facing evaluation, the lower the level of student self-efficacy, and vice versa.